EVALUASI KEPUASAN PELANGGAN PADA JASA PERPUSTAKAAN DAN ISSN PDII-LIPI - Nashihuddin, Wahid; Ridho Aulianto, Dwi (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2015)
The purposes of this study are: (a) determine the level of customer satisfaction in library and ISSN services; (b) determine customers feedback in improving the quality of library and ISSN services. Type of data this study is quantitative. Data were collected by distributing Survei Kepuasan Masyarakat (SKM) questionnaires. There are nine indicators in SKM: (1) compliance with the service requirements; (2) easy of servicing procedures; (3) the timeliness of service; (4) the suitability of the service charge; (5) product assurance services; (6) the competence of service personnel; (7) the behavior of the service personnel; (8) clear intimation of service; and (9) the handling of complaints, suggestions, and feedback of services. SKM questionnaire distributed to 60 respondents who have received services from the concierge of library and ISSN service. The data are interpreted with a frequency distribution table. Each indicator item in SKM has processed by the value/score of the class interval system. Results of this study indicated that the information service on library and ISSN are satisfactory of customer. The results based on customer survey uses nine indicators of SKM. Most respondents who become customers of the library and ISSN feel satisfied, the number of 43 respondents (71,7%) said they were satisfied and 11 respondents (18,3%) expressed great satisfaction with the services. If viewed from the service unit, there are 25 respondents (83,33%) as a subscribers of library services and 18 respondents (60%) as a ISSN customers whose are satisfied with the those services. However, despite on the results of SKM had been satisfaction, the institution must be to improve the quality system of services ongoing basis. This is done to reduce or eliminate various forms of complaints from customers.